This is Malaysia - Moore, Wendy (New Holland, 1995)
This study looks at a country that has long attracted explorers, scientists, traders and historians. It features Malaysia's chequered history, the Malaysian peoples, the diversity of the country's flora and fauna, its unchanging landscape, and Malaysia's development and survival.